Hepatoprotective effect of dried and fermented virgin coconut oils against carbon tetrachloride and paracetamol-induced liver damage in vivo / Mohd Salleh Rofiee - Rofiee, Mohd Salleh (2011)
Virgin coconut oil (VCO), famously known in Malaysia as 'minyak kelapa dara', is a type of coconut oil that has gained a lot of attention recently due to various claimed of medicinal values. The present study was carried out on two types of VCOs, labelled as VCOA and VCOB, to determine its toxicity, hepatoprotective property and mechanism of action. The acute toxicity study was carried out by oral administration of 10 ml/kg VCOA or VCOB to normal rats for 7 days. The hepatoprotective property was determine using carbon tetrachloride (CCU)- and paracetamol-induced liver damage. The mechanism of hepatoprotection of VCOs was determine using an inducer, Phenobarbital (PB), and an inhibitor, SKF 525A, of cytochrome P450 (CYP), against paracetamol-induced liver damage. From the data obtained both types of VCOs did not show any sign of toxicity to the animal. The result on hepatoprotective of VCO A and VCO B against CCU induce liver damage did not show any significant different because CCI4 at 1.5ml/kg orally did not induce extremely liver damage compare to PCM. Both types of VCOs were found to produce hepatoprotective effect against paracetamol-induced liver damage at the volume of 10 ml/kg. This finding is confirmed by significant (PO.05) reduction in body weight, liver weight, concentrations of liver enzymes, namely alanine aminotransferase (ALT), aspartate aminotansferase (AST) and alkaline phosphatase (ALP), and cell viability were increase compared to group treated with paracetamol alone. Histopathology study of rat's liver treated with PCM only show necrosis but pre-treated with lOml/kg both VCOs showed normal architecture of the liver. The inhibition of CYP may be a key role in the mechanism of hepatotoprotective effect of both VCOs against the paracetamol-induced liver damage.